2015
DOI: 10.1111/jocn.13013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a feeding intervention in patients with Alzheimer's disease and dysphagia

Abstract: The significant improvement in eating/feeding measures suggest that this feeding intervention model could be developed as a feeding skills programme to improve both the eating/feeding care by nursing staff and the eating/feeding abilities and nutritional status of Alzheimer's disease patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 21 publications
0
51
0
3
Order By: Relevance
“…Providing high‐quality environmental stimulation along with appropriate assistance and interaction is essential to promote pace of food intake in this population. Multi‐level efforts targeting the resident, the caregiver, the food and dining environment, as well as the organizational context, are needed to ensure a successful mealtime experience (Liu et al, ) and have demonstrated feasibility as well as great potential to reduce feeding difficulty and improve food intake in residents with dementia and dysphagia (Chen et al, ). Clinical caregivers are critically positioned to provide optimal mealtime care for residents with dementia and caregiver–resident interaction affects food intake.…”
Section: Discussionmentioning
confidence: 99%
“…Providing high‐quality environmental stimulation along with appropriate assistance and interaction is essential to promote pace of food intake in this population. Multi‐level efforts targeting the resident, the caregiver, the food and dining environment, as well as the organizational context, are needed to ensure a successful mealtime experience (Liu et al, ) and have demonstrated feasibility as well as great potential to reduce feeding difficulty and improve food intake in residents with dementia and dysphagia (Chen et al, ). Clinical caregivers are critically positioned to provide optimal mealtime care for residents with dementia and caregiver–resident interaction affects food intake.…”
Section: Discussionmentioning
confidence: 99%
“…Methods to deliver training included the internet (Batchelor-Murphy et al, 2015), lectures (Chen et al, 2016;Faxen-Irving et al, 2002;Mamhidir et al, 2007;Suominen et al, 2007), in-service coaching (Altus et al, 2002;Chang & Lin, 2005;Chen et al, 2016;Mamhidir et al, 2007), group work (Batchelor-Murphy et al, 2015;Charras & Frémontier, 2010;Christensson et al, 2003;Mamhidir et al, 2007;Suominen et al, 2007), written materials (Chang & Lin, 2005, Chen et al, 2016Christensson et al, 2003), and video footage (Batchelor-Murphy et al, 2015;Mamhidir et al, 2007;Roberts & Durnbaugh, 2002).…”
Section: Methods Of Deliverymentioning
confidence: 99%
“…All of the studies were carried out in long-term care settings. In regards to quality appraisal of the training studies, two studies scored 100% using the MMAT (Chen et al, 2016;Van Ort & Phillips, 1995), three studies scored 75% (Batchelor-Murphy et al, 2015;Chang & Lin, 2005;Faxen-Irving et al, 2002), six scored 50% (Altus et al, 2002;Christensson et al, 2003;Mamhidir et al, 2007;Perivolaris et al, 2006;Roberts & Durnbaugh, 2002;Suominen et al, 2007), and one scored 0% (Charras & Frémontier, 2010). The most common unmet criterion across the studies was "Are participants (organizations) recruited in a way that minimizes selection bias?".…”
Section: Characteristics and Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…35 Enteral tube feeding is inevitable when patients with end-stage AD stop eating or experience significant difficulty in swallowing.…”
Section: Food Refusalmentioning
confidence: 99%